The complete mitogenome of three continuous generations of ‘Rongfu’: a crucial Saccharina cultivation variety. Issue 1 (2nd January 2019) - Yu, Yahui; Zhang, Jing; Jia, Shangang; Wang, Guoliang; Liu, Tao; Wang, Xumin
Abstract: Here, the complete mitogenome of three generations of ‘Rongfu’ were sequenced. The three genome sequences were exactly the same, whose circular genomes were all 37, 638 bp in length, consisting of 35 protein-coding genes, 25 transfer RNA genes, 3 ribosomal RNA genes, and 3 open reading frames. The genome composition with A + T bias (64.66%) and gene arrangement was similar to those Saccharina species. The phylogenetic analysis showed that the three generations of ‘Rongfu’, ‘Rongfu’ in NCBI, and ‘Fujian’ in NCBI were clustered together, which will reveal the genetic and evolutionary characteristics at genomic level.